A study of street trees in 16th of October Street in Lattakia City and a proposal to improve them by default using Photoshop (Latakia University Journal -Biological Sciences Series, 2023)
This research was conducted during the years 2020-2021 in one of the main streets of Lattakia city, where the natural and service elements of coordination were limited, and virtual landscapes were designed that improved the actual reality of the studied street using Photoshop, and the opinion of the local residents was taken about the planted species and landscapes before and after modification..The results showed that the trees in the street did not achieve the ideal percentage of each type, genus and species of the total trees on the street, in addition to the presence of interruptions within the tree rowsThe results also showed the presence of obvious defects and distortions within the tree rows, such as some cases of the longitudinal axis tilt of the tree trunks from the plumb, the overlap of some tree crowns, pathological injuries, human practices, and others. And interest on the part of the population in changing the general landscape and planting species that are resistant to noise and pollution